Public Communication of COVID-19 Prevention in Vulnerable and Marginal Groups Towards Strong and Prosperous Family Resilience in Sidoarjo - Sri Warjiyati; Nurul Asiya Nadifah; Marli Candra (Jurnal Hukum Volkgeist, 2022)
The title of this research is "COVID-19 Prevention Public Communication in Vulnerable and Marginal Groups Towards Resilience of Strong and Prosperous Families in Siodarjo" to answer questions related to the urgency of public communication, public communication patterns, public communication strategies, public communication approaches, the influence of family resilience, and how are the efforts of the marginalized to prevent the spread of the COVID-19 virus. The method in this study uses socio-legal research, which is a study of the law using a legal and social science approach. Then the data is analyzed qualitatively to obtain a complete picture of understanding regarding the study of public communication to prevent COVID-19 in vulnerable and marginal groups towards the resilience of a solid and prosperous family (analysis of the perspective of human rights in Sidoarjo). The results obtained from this study indicate that Sidoarjo has utilized and optimized the role of this technology. One way to achieve success in public communication activities is an effective and collaborative communication strategy implemented in Sidoarjo. In addition, efforts to increase family resilience are also optimizing to overcome the spread of the COVID-19 virus, which is becoming an epidemic throughout the region.